Integrated Fragility Hip Fracture Program: A Model for High Quality Care. Issue 8 (19th February 2020) - Morris, Jensa C; Moore, Anne; Kahan, Joseph; Shapiro, Marc; Li, Jinlei; Spadaccino, Brooke; Baumgaertner, Michael; O'Connor, Mary I
Abstract : BACKGROUND: Hip fractures are a significant cause of morbidity and mortality among elderly patients. Coordinated multidisciplinary care is required to optimize medical outcomes. OBJECTIVE: To determine the effect of the implementation of standardized, evidence‐based protocols on clinical outcomes and mortality in patients with fragility hip fractures. INTERVENTIONS: A multidisciplinary group was convened to define best practices in fragility hip fracture care and implement a fragility hip fracture clinical protocol at Yale‐New Haven Hospital. Clinical outcomes in 2015, prior to program initiation, were compared with 2018, after the program was well established. MAIN OUTCOMES AND MEASURES: Measured outcomes included 30‐day mortality, blood transfusion utilization, adverse effects of drugs, venous thromboembolic complications, sepsis, myocardial infarction, mechanical surgical fixation complications during the index admission, length of stay, 30‐day readmission, unexpected return to the operating room (OR) and time to the OR. RESULTS: The implementation of the Integrated Fragility Hip Fracture Program was associated with significant reductions in 30‐day mortality from 8.0% in 2015 to 2.8% in 2018 ( P = .001). Significant reductions were also seen in use of blood transfusions (46.6% to 28.1%; P < .001), adverse effects of drugs (4.0% to 0%; P < .001), length of stay (5.12 to 4.47 days; P = .004), unexpected return to the OR (5.1% to 0%; P < .001), and time to the OR <24 hours (41.8% to 55.0%, P = .001). CONCLUSIONS: An Integrated Fragility Hip Fracture Program using multidisciplinary care, physician and nursing engagement, evidence‐based protocols, data tracking with feedback, and accountability can reduce mortality and improve clinical outcomes in patients with hip fractures.